Tinjauan Yuridis Tindak Pidana Pencucian Uang pada Transaksi Digital Cryptocurrenncy - Lumaing, Engeli Yuliana; Purba, Chastro; Moga, Julian Valentino; Metusalach, Wanli; Legi, Rizky; Dakhi, Robin (Jurnal Social Science, 2024)
Money laundering through crypto assets in Indonesia is a complex and challenging problem for law enforcement. This study aims to identify the challenges law enforcement faces against money laundering practices that utilize cryptocurrency. The research method used is qualitative analysis with a case study approach and interviews with experts in law and finance. The study results show that although there are regulations governing crypto asset transactions, money laundering practices are still rampant due to the anonymous nature and complexity of blockchain technology. Law enforcement has difficulty in tracking transactions and identifying perpetrators, especially due to the many loopholes in the law. Cooperation between government agencies and law enforcement is needed to improve the effectiveness of supervision and law enforcement against money laundering crimes using cryptocurrency. This study also recommends the need for clearer and more comprehensive regulations regarding the use of cryptocurrency in Indonesia to prevent further misuse.